1988
DOI: 10.1007/bf01964237
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of beta-lactam resistance inHaemophilus influenzae

Abstract: Haemophilus influenzae has become increasingly resistant to beta-lactam antibiotics. Three major mechanisms, both enzymatic and non-enzymatic, are involved. Enzymatic resistance is mainly due to production of a TEM-1 plasmid-mediated beta-lactamase, and in some cases to a new enzyme ROB-1. Of the non-enzymatic mechanisms, decreased permeability due to alteration of outer membrane proteins seems to be rare in comparison to decreased affinity of penicillin-binding proteins for beta-lactam antibiotics. Enzymatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Our data indicate little resistance to the cephalosporin class of P-lactams by the original and transconjugant P. haemolytica isolates, but higher resistance of E. coli transformants containing the ApR plasmids, particularly pPH843. The sensitivity and substrate profiles of the ROB-and TEM-type /Ilactamases have been reported to be similar (Guttmann et al, 1988) and this was confirmed in the present study (Tables 4 and 5). The ROB-1 P-lactamase has been differentiated from the TEM-1 enzyme by its higher PI and its ability to hydrolyse ampicillin more rapidly and cephaloridine more slowly (Rubin et al, 1981).…”
Section: Discussionsupporting
confidence: 80%
“…Our data indicate little resistance to the cephalosporin class of P-lactams by the original and transconjugant P. haemolytica isolates, but higher resistance of E. coli transformants containing the ApR plasmids, particularly pPH843. The sensitivity and substrate profiles of the ROB-and TEM-type /Ilactamases have been reported to be similar (Guttmann et al, 1988) and this was confirmed in the present study (Tables 4 and 5). The ROB-1 P-lactamase has been differentiated from the TEM-1 enzyme by its higher PI and its ability to hydrolyse ampicillin more rapidly and cephaloridine more slowly (Rubin et al, 1981).…”
Section: Discussionsupporting
confidence: 80%
“…There is evidence that there has been some increase in the occurrence in the UK of these strains, al though the prevalence generally remains low [14]. In France [22], non-enzymatic resistances have been found increasingly, occurring in about 2^f% of the H. influenzae strains. The most frequent non-enzymatic mechanism of resistance is based on an alteration of penicil lin-binding proteins 4 and 5 [22].…”
Section: Discussionmentioning
confidence: 99%
“…In France [22], non-enzymatic resistances have been found increasingly, occurring in about 2^f% of the H. influenzae strains. The most frequent non-enzymatic mechanism of resistance is based on an alteration of penicil lin-binding proteins 4 and 5 [22]. Decreased permeability by alteration of porins has been reported only rarely [22], Infections due to these strains are being reported more fre quently than before [8,23,24], It has been agreed that the different pre scription policies and treatment strategies em ployed in different regions might influence the resistance rates and patterns of resistance in H. infuienzae.…”
Section: Discussionmentioning
confidence: 99%
“…5,13 Ampicillin resistance mostly recognized in type b strains is mainly due to the production of a ß-lactamase-type TEMI enzyme. 15 Nonenzymatic mechanisms of resistance to ampicillin and other ß-lactam antibiotics include decreased outer membrane permeability and alterations in penicillin-binding proteins 4 and 5. 15 Resistance to chloramphenicol is due to the production of a chloramphenicol acetyl-transferase enzyme and is usually related to tetracycline resistance.…”
Section: Discussionmentioning
confidence: 99%
“…15 Nonenzymatic mechanisms of resistance to ampicillin and other ß-lactam antibiotics include decreased outer membrane permeability and alterations in penicillin-binding proteins 4 and 5. 15 Resistance to chloramphenicol is due to the production of a chloramphenicol acetyl-transferase enzyme and is usually related to tetracycline resistance. 13 While resistance to ampicillin is usually plasmid mediated, 16 that of trimethoprim is mediated by a gene located on the chromosome.…”
Section: Discussionmentioning
confidence: 99%